Rekonstruksi Islamisasi Pedalaman: Model Berbasis Masjid dan Terintegrasi dengan Tradisi dari Banua Lima, Kalimantan Selatan - Jamalie, Zulfa; Wibowo, Fasih (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2025)
The history of Islamic dissemination in Banua Lima particularly along the Batang Alai River Basin in Barabai remains poorly documented, resulting in a fragmented understanding of early Islamization in the upstream region compared to the more extensively recorded coastal areas. This study aims to reconstruct the development pattern of Islam in Banua Lima by examining historical traces, the role of sacred mosques, local religious figures, and the acculturation of pre-Islamic traditions. Employing a historical-social approach with heuristic, verification, interpretation, and historiographical stages, data were collected through archival studies, oral histories, site observation of heritage mosques, and documentation of cultural rituals. The findings indicate that Islam spread through three fundamental mechanisms: the establishment of mosques as centers of religious activities, the empowerment of local figures as key agents of da'wah, and the integration of indigenous traditions such as Baayun Maulid and Batumbang—into Islamic practice. Heritage mosques in Palajau, Banua Halat, Banua Lawas, and surrounding areas serve as material evidence of the da'wah mission led by Khatib Dayan. The study concludes that the Islamization process in Banua Lima was peaceful, adaptive, and collaborative, forming a da'wah model that remains contextually relevant for contemporary local communities. Further research and preservation of historical mosques and cultural traditions are recommended as strategic efforts to maintain the Islamic historical legacy in South Kalimantan.